Strength and conditioning practices in rowing - Gee, T. I.; Peter, D.; Berger, N. J.; Golby, J.; Thompson, K. G. (The Journal of Strength and Conditioning Research, 2011)
There is limited published research on the practices of strength and conditioning (S &C) coaches in Great Britain. Information about training program design would be useful in developing models of good practice and ecologically valid intervention studies. The aim of this research was to quantify the training practices of coaches responsible for the S&C of rowing athletes. A questionnaire was developed that consisted of 6 sections: (a) personal details, (b) physical testing, (c) strength and power development, (d) flexibility development, (e) unique aspects of the program, and (f) any further relevant comments regarding the athletes prescribed training program. Twenty-two rowing and 10 S&C coaches with an average of 10.5 ± 7.2 years' experience agreed to complete the questionnaire. Approximately, 34% coached rowers of Olympic standard, 34% coached national standard, 3% coached regional standard, 19% coached club standard, and 10% coached university standard rowers. All coaches agreed that strength training enhanced rowing performance and the majority (74%) indicated that athletes' strength trained 2-3 times a week. Almost all coaches (94%) reported their rowers performed strength training, with 81% using Olympic lifting, and 91% employing a periodized training model. The clean (63%) and squat (27%) were rated the most important prescribed exercises. Approximately 50% of coaches used plyometrics such as depth jumps, box drills, and standing jumps. Ninety-four percent indicated they conducted physical testing on their rowers, typically assessing cardiovascular endurance (80%), muscular power (70%), muscular strength (70%), and anaerobic capacity (57%). This research represents the only published survey to date on the S&C practices in rowing within Great Britain.